Luminescence Properties and Decay Kinetics of Mn 2+ and Eu 3+ Co-Dopant Ions in MgGa 2 O 4 Ceramics - Luchechko, A.; Zhydachevskyy, Ya.; Sugak, D.; Kravets, O.; Martynyuk, N.; Popov, Anatoli I.; Ubizskii, S.; Suchocki, A. (Sciendo, 2018)
The MgGa 2 O 4 ceramics co-doped with Mn 2+ and Eu 3+ ions were synthesized via a higherature solid-state reaction technique. The samples with various Eu 3+ concentrations were characterised using high-resolution photoluminescence (PL) spectroscopy. The PL spectra show weak matrix emission in a blue spectral region with dominant excitation band around 380 nm. Manganese ions are highly excited deeply in UV region and exhibit emission band peaked at 502 nm. The Eu 3+ ions show characteristic f-f excitation and emission lines. The energy transfer between host defects and activator ions was observed. Luminescence decay curves of Mn 2+ and Eu 3+ emission showed complex kinetics with both Eu 3+ -ion concentration and excitation wavelength changes.
A. Luchechko gratefully acknowledges a grant from the Institute of Physics PAS for a research visit to the institute, while A.I. Popov has been supported by project LZP-2018/1-0214 from the Latvian Council of Science.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; decay kinetics; energy transfer; europium (Eu 3+ ) and manganese (Mn 2+ ) ions; magnesium gallate MgGa 2 O 4; photoluminescence